2007
DOI: 10.1089/acm.2007.7166
|View full text |Cite
|
Sign up to set email alerts
|

Biopsychosocial Effects ofQigongas a Mindful Exercise for People with Anxiety Disorders: A Speculative Review

Abstract: In view of the inadequacies of mainstream treatments for anxiety disorders, we suggest that qigong, an ancient oriental mindful exercise, may be a useful adjunctive treatment. We base this on a biopsychosocial model for health. Evidence suggests that the benefits of exercise on personal well-being can be explained using six theories: cognitive behaviour; distraction; social interaction; cardiovascular fitness; amine; and endorphin theories. To date, not much has been done to employ these theories to analyze th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 64 publications
(72 reference statements)
1
52
0
1
Order By: Relevance
“…[1][2][3][4][5] Ultimately, the deleterious effects of stress generalize to the workplace, leading to professional burnout with attendant declines in job productivity and increased absenteeism. 6 Among hospital staff in particular, there is evidence of elevated rates of psychologic stress and stress-related disorders.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] Ultimately, the deleterious effects of stress generalize to the workplace, leading to professional burnout with attendant declines in job productivity and increased absenteeism. 6 Among hospital staff in particular, there is evidence of elevated rates of psychologic stress and stress-related disorders.…”
mentioning
confidence: 99%
“…From the perspective of a mind-body approach, the psycho-social effect of Qi Gong was hypothesized by Tsang et al (2002) as they argued that Qi Gong, as a form of Chinese therapeutics, has the effect of improving life quality and overall wellbeing. Chow and Tsang (2007) have suggested that Qi Gong can be considered as an alternative therapy to help to meet the increasing demand for non-pharmacologic modalities in achieving holistic health for those suffering from anxiety in the general population (Chow and Tsang, 2007). Mental wellbeing can be achieved due to Qi Gong movements as they may reduce tensions, and regulate the body's internal balance (Ryu et al, 1996(Ryu et al, , 1997Wu et al, 1999;Jones, 2001).…”
Section: Qi Gong and Healthmentioning
confidence: 99%
“…Qigong is ancient chinese exercise including movement focusing on breathing, a meditative state of mind, and relaxation [1]. Focus on breathing during Qigong practice may bring the mind to a restful state and oxygenation and/or energy to the body [1].…”
Section: Introductionmentioning
confidence: 99%
“…Focus on breathing during Qigong practice may bring the mind to a restful state and oxygenation and/or energy to the body [1]. Altering the breathing pattern may be associated with changing of the autonomic nervous system function [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation